Heat Shock Causes Lower Plasmodium Infection Rates in Anopheles albimanus - Condé, Renaud; Hernandez-Torres, Erika; Claudio-Piedras, Fabiola; Recio-Tótoro, Benito; Maya-Maldonado, Krystal; Cardoso-Jaime, Victor; Lanz-Mendoza, Humberto (Frontiers in Immunology, 2021)
The immune response of Anopheles mosquitoes to Plasmodium invasion has been extensively studied and shown to be mediated mainly by the nitric oxide synthase (NOS), dual oxidase (DUOX), phenoloxidase (PO), and antimicrobial peptides activity. Here, we studied the correlation between a heat shock insult, transcription of immune response genes, and subsequent susceptibility to Plasmodium berghei infection in Anopheles albimanus. We found that transcript levels of many immune genes were drastically affected by the thermal stress, either positively or negatively. Furthermore, the transcription of genes associated with modifications of nucleic acid methylation were affected, suggesting an increment in both DNA and RNA methylation. The heat shock increased PO and NOS activity in the hemolymph, as well as the transcription of several immune genes. As consequence, we observed that heat shock increased the resistance of mosquitoes to Plasmodium invasion. The data provided here could help the understanding of infection transmission under the ever more common heat waves.